The next world war : tribes, cities, nations and ecological decline - Woodbridge, Roy M. (University of Toronto Press, 2004)
Pre-occupied with the war on terrorism, we have lost sight of a more dangerous enemy of social peace and progress - the inability of the world's people to access the ecological goods and services they need to maintain and build their societies. By 2025, the combined demands of continued economic growth and the reduction of global poverty will require, annually, the ecological equivalent of three or four earths. Like the tribes, cities, and nations of earlier times, we can fight our neighbours for privileged access to declining ecosystem goods and services. This confrontation will inevitably pit the wealthy beneficiaries of the global economy against the billions of excluded, and lead to accelerated ecological collapse, the derailment of growth, and social chaos. The only alternative to this dismal prospect is to mobilize on a scale as if for war in order to meet this provisioning challenge on the battlefields of directed technological innovation.